Prognosis and therapeutic significance of IGF-1R-related signaling pathway gene signature in glioma - Liu, Zhen; Yang, Liangwang; Wu, Wenqi; Chen, Zejun; Xie, Zhengxing; Shi, Daoming; Cai, Ning; Zhuo, Shenghua (Frontiers in Cell and Developmental Biology, 2024)
Background Glioma is the most common cancer of the central nervous system with poor therapeutic response and clinical prognosis. Insulin-like growth factor 1 receptor (IGF-1R) signaling is implicated in tumor development and progression and induces apoptosis of cancer cells following functional inhibition. However, the relationship between the IGF-1R-related signaling pathway genes and glioma prognosis or immunotherapy/chemotherapy is poorly understood. Methods LASSO–Cox regression was employed to develop a 16-gene risk signature in the TCGA-GBMLGG cohort, and all patients with glioma were divided into low-risk and high-risk subgroups. The relationships between the risk signature and the tumor immune microenvironment (TIME), immunotherapy response, and chemotherapy response were then analyzed. Immunohistochemistry was used to evaluate the HSP90B1 level in clinical glioma tissue. Results The gene risk signature yielded superior predictive efficacy in prognosis (5-year area under the curve: 0.875) and can therefore serve as an independent prognostic indicator in patients with glioma. The high-risk subgroup exhibited abundant immune infltration and elevated immune checkpoint gene expression within the TIME. Subsequent analysis revealed that patients in the high-risk subgroup benefited more from chemotherapy. Immunohistochemical analysis confirmed that HSP90B1 was overexpressed in glioma, with significantly higher levels observed in glioblastoma than in astrocytoma or oligodendrocytoma. Conclusion The newly identified 16-gene risk signature demonstrates a robust predictive capacity for glioma prognosis and plays a pivotal role in the TIME, thereby offering valuable insights for the exploration of novel biomarkers and targeted therapeutics.